Comparison of phytase activity in roots of wheat varieties grown under different phosphorus conditions - Mohsin, Samreen; Malik, Kauser Abdulla; Maqbool, Asma (Research in Biotechnology, 2015)
Phosphorus (P) is a vital macronutrient for plant growth but it is poorly available to plant roots as a significant amount of soil P is present in the form of phytate. To overcome phosphorus deficiency, wheat is capable of producing phytase. In the present study, six Pakistani wheat varieties (Faisalabad-2008, Sehar-2006, Pak-81, Punjab-11, ASS-11, VII-83) were evaluated for their phytase activity, protein and total phosphorus content of shoots and roots under three phosphorus conditions. All wheat varieties exhibited a differential ability to produce phytase in different P conditions. The highest phytase activity was observed in root extracts (0.781U/g), external root solution (0.0972 U/g) and intact roots (0.0417U/g) of Pak-81 when grown in the presence of phytate. Highest protein content (44 Î¼g), shoot (176.25 Î¼g) and root (111.62 Î¼g) phosphate content was observed in Pb-11 and VIII-83, respectively in the presence of inorganic phosphate. Results indicate that wheat varieties are unable to fulfill their P requirements, thus it is necessary to augment phytase production in wheat via breeding methods or transgenic approach.